2017
DOI: 10.1111/epi.13939
|View full text |Cite
|
Sign up to set email alerts
|

Considerations in performing and analyzing the responses of cortico‐cortical evoked potentials in stereo‐EEG

Abstract: SummaryThis review aims to highlight key considerations when performing cortico-cortical evoked potentials (CCEPs) using stereo-electroencephalography (SEEG) for network mapping and show its clinical applicability to presurgical evaluations. The parameters for performing stimulation and safety aspects have been investigated in electrocorticography (ECoG) and deep brain stimulation (DBS), but not as extensively in SEEG. A review of current literature was performed, with an attempt made to emphasize practical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 74 publications
2
45
0
Order By: Relevance
“…The stimulation is a biphasic charge‐balanced stimulation waveform. Given the contact surface and volume (Dixi or Alcis electrodes, approximately 0.05 cm²), the charge density was between 9 and 18 μC/cm², which is in the safety range (see Appendix S1) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stimulation is a biphasic charge‐balanced stimulation waveform. Given the contact surface and volume (Dixi or Alcis electrodes, approximately 0.05 cm²), the charge density was between 9 and 18 μC/cm², which is in the safety range (see Appendix S1) …”
Section: Methodsmentioning
confidence: 99%
“…Given the contact surface and volume (Dixi or Alcis electrodes, approximately 0.05 cm²), the charge density was between 9 and 18 μC/ cm², which is in the safety range (see Appendix S1). 13,14 We will refer of this type of seizure as a pulvinar-stimulated (Puv[+]) seizure.…”
Section: Effect Of Pum Stimulation On Seizures Induced By Hippocampmentioning
confidence: 99%
“…The lack of standardized stimulation parameters limits interpretation of the data, reducing its clinical utility [5,13,14]. The amplitude of stimulation may be 0.5 mA to >10 mA [6,9], which changes the charge density per phase that the tissue experiences [15].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found that there were different occurrence rates and CCEP amplitudes in patients with generalized epilepsy and those with focal epilepsy (33). We did not on studying this difference, because there were multiple seizure types in patients with TSC, and most of the patients suffered generalized seizure and focal seizure at the same time.…”
Section: Discussionmentioning
confidence: 99%